Assessment of explosibility and explosion severity of rice flour at different concentration and ignition time. (14th November 2019) - Wan Sulaiman, Wan Zaiton; Mohd Idris, Mohd Fadzil; Gimbun, Jolius; Sulaiman, Siti Zubaidah
Abstract: This article presents a dust explosion characteristics of commercial rice flour at different concentration and ignition time. The rice flour with a moisture content of 7.79% (undried) and a mean diameter of D 50 = 28.77 μm was used in this work. The moisture in the rice flour was further reduced by oven drying to 2.47% (dried) and both samples were tested for comparison. Experiments were performed in a 20 L spherical explosion chamber to obtain the maximum explosion overpressure ( P max ), rate of pressure rise ( dP / dT ), minimum explosibility concentration (MEC), and deflagration index ( K st ) of undried and dried commercial rice flour. The dust samples and air mixtures were ignited by two chemical ignitors at the ignition time ( t v ) of 60 and 100 ms. The propagation of pressure wave during the explosion process was measured by the piezoelectric pressure sensor. The P max for undried and dried rice flour at t v of 60 ms were found at 11.25 bar and 8.6 bar, respectively. The P max was obtained at the highest concentration of dust (1000 kg/m 3 ). The highest pressure rise of undried sample was obtained at 81 bar/s whereas for dried sample the highest value was obtained at 98 bar/s. MEC of undried sample was found at 600 kg/m 3 and the dried sample at 500 kg/m 3 . The K st of dried rice flour at ignition time 60 ms was found to be the highest at 26.6 bar m/s. It was found that the severity of the dust explosion increases proportionally with the dust concentration. Rice flour with higher moisture content has a lower explosion severity, than that of dried sample. Findings from this work provide a useful safety information about the severity and explosibility of rice flour, for which unsafe handling and operation may be minimized.